Comprehensive Agrarian Reform Program (CARP) and the Fisheries, Livestock and Crop Sectors: Adjustments in the Pasture Leases - Achilles Costales (Philippine Institute for Development Studies (PIDS), 1994)
This study focuses on the responses of pasture leases to the possibility of agrarian reforms by using the survey of 145 pasture leases in Masbate, Bukidnon and South Cotabato where pasture leases where concentrated. This paper relies mainly on the descriptive method of analysis. Results indicate the opening up of pasture leases to bidding for the most productive use of the land subject to the clear-cut regulations that such activities be environmentally and economically sustainable.
Keywords: 330; land management; environmental issues; Comprehensive Agrarian Reform Program (CARP); crop production; livestock commodities; pasture lands